Late Presentation of Unsafe Abortion after 5 Years of Procedure - Prasanta Kumar Nayak; Subarna Mitra; Alaganandam Padma; Sarita Agrawal (Case Reports in Obstetrics and Gynecology)
A majority of the unsafe abortions are performed by untrained birth attendants or quacks leading to complications in a large proportion of these cases. Complications like bowel injury, bladder injury, uterine perforation, and septic abortion are mostly caused by unskilled hands and are detected immediately or within few days of the procedure, owing to the need for tertiary level care. Here we present a very interesting case of unsafe abortion induced by a Ryle’s tube in a 32-year-old lady, which was diagnosed five years after the procedure. Considering its atypical presentation, it is the first case of its kind in the literature. The details of the case and its management are described along with appropriate pictures.